Exosome-mediated dual drug delivery of curcumin and methylene blue for enhanced cognitive function and mechanistic elucidation in Alzheimer’s disease therapy - Yang, Dongxin; Deng, Zhuofen; Zhou, Hai; Zhang, Qingshang; Zhang, Xibing; Gong, Jun (Frontiers in Cell and Developmental Biology, 2025)
Alzheimer’s disease (AD) is one of the neurodegenerative disorders, characterized by complex pathogenic mechanisms, including the deposition of beta-amyloid protein and hyperphosphorylation of Tau protein. There is currently a lack of effective therapeutic approaches for AD treatment. The aim of this study was to design exosomes (EXO) as a specifically designed carrier able to carry Curcumin (Cur) and Methylene Blue (MB) to improve cognitive function and to elucidate its underlying mechanisms. Our study results indicated that EXO-Cur+MB inhibited Tau protein phosphorylation by activating the AKT/GSK-3β pathway, while reversing cognitive dysfunction in AD mice by reducing apoptosis induced by okadaic acid (OA). Thus, our results suggested that EXO-Cur+MB would be of potential use for the treatment of AD.